PENGARUH FAKTOR LINGKUNGAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU DI PASAR TRADISIONAL DAN MODERN (Studi Kasus: Pasar Anyar Bogor dan Giant Botani Square) - Dewi Nuraini; Mukhamad Najib (Faculty of Economics and Business Udayana University, 2015)
The aims of this research are to compare characteristic differences of milk consumers in traditional and modern market, to analyze the influence of environmental factor (cultural, social class, individual, family and situation) on milk consumer buying decision in traditional and modern market, and to analyze the dominant sub-factors in influencing consumer to buy milk product in both market. This research was conducted in Pasar Anyar Bogor and Giant Hypermart Botani Square Bogor from February until April 2015. The data used was primary data collected through questionnaire and analyzed by using Structural Equation Modeling (SEM) through Partial Least Square (PLS) approach.The results show that individual factor and family factors emerge as environmental sub-factor which affect positively buying decision of milk product both in traditional and modern market. As a whole, the impact environmental factor on milk consumer buying decision is 72,6% in traditional market and 78% in modern market